Modeling and Simulation of Thermal Behaviour and Clad Geometry Evaluation during Laser Cladding - Diwakar, Vikas; Sharma, Ashwani; Chaudhari, Abhimanyu; Yusufzai, Mohd Zaheer Khan; Vashista, Meghanshu (United Scientific Group, 2023)
It is very important to get the desired clad geometry characteristics and quality during the laser cladding. The thermal behaviour and clad geometry evolution of Inconel 718 during laser cladding (LC) have been studied using an enhanced three-dimensional (3-D) finite element model which includes attenuation of the laser heat flux due to the convection as well as surface to ambient radiation. The cladding layer formation process is simulated and by applying the temperature-based decision-making approach to evaluate the cladding geometry which is very important to get high quality of the cladded layers on the substrate. During the simulation, observed that more heat is transferred into to the substrate at the higher laser power which results more dilution percentage and at the same time cross sectional view of the cladded powder showed higher temperature distribution when move downward from the surface of the substrate. With increasing laser power, the clad width, penetration depth reference to the surface and clad width increases at constant scanning speed. The dilution can be minimized by varying the scanning speed and laser power simultaneously.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.
Keywords: Clad geometry; Laser cladding; Thermal behaviour